Recovering indigenous inscriptions of meaning from the colonial novel: A re-reading of the spatial archetypes in Joseph Conrad’s Lord Jim - Ahmad, Siti Nuraishah (2011)
This paper discusses an alternative reading practice of the colonial novel (Zawiah 2003) that puts the re(-) presentation of space in such novels under scrutiny. Informed firstly by Jungian archetypal criticism and secondly, by Gayatri Spivak’s concept of ‘worlding’ (1999), it examines the re-presentation of Malaya’s geospatial features – the sea, mountains, forests – as archetypes in the novel Lord Jim (1900) by Joseph Conrad. These archetypal images, I argue, erase the indigenous meanings already inscribed onto Malaya’s geospatial features, in the colonial project of worlding Malaya. However, by peeling away the layers of Western inscriptions of meaning onto Malaya’s geospatial features, the contemporary, post-colonial reader might recover the various meanings endowed on Malaya by its native inhabitants. This alternative reading practice thus enables the reader to discover the diversity of meanings that can and have been given to geospatial features, as opposed to the West’s unilateral act of worlding other worlds.